An analysis of the semantic-discursive organization of controversy in contrapunteos llaneros (Dissertare, 2017)
The present work is located in the line of investigation discourse analysis and in agreement, it has a descriptive character. Its general objective was to analyze the semantic-discursive organization of the controversy in Venezuelan  contrapunteos llaneros, which was carried out based on three specific objectives, the first of which was aimed at describing the textual organization of the controversy; the second oriented to study the discursive organization of the controversy regarding its phases and strategies of interaction and a third specific objective dedicated to examine in the semantic organization of the controversy the themes, motives and figures used for the construction of the image of the coplero . The corpus was made up of fifteen (15) contrapunteos llaneros. From a theoretical point of view, this study was based on the work of Díaz-Pimienta (1998) on improvisation and suddenness; for the study of the textual organization it was based on the work carried out by Bolívar (2005), and for the semantic organization of the controversy the investigations of Greimas and Courtés (1990) were used. Based on these considerations, it was concluded that the controversy allows two turn-based followers. Also, the controversy goes through three zones for its discursive organization, which are the scoring zone, thematic-core zone and the outcome zone; also the llanero builds his image based on themes, motifs and figures, which highlights his pride in being Venezuelan, his dedication to work and his strength.
Keywords: discourse analysis; semantic-discursive organization; controversy; contrapunteos llaneros; coplero